N2M2 (NOA-20) phase I/II trial of molecularly matched targeted therapies plus radiotherapy in patients with newly diagnosed non-MGMT hypermethylated glioblastoma - Wick, Wolfgang; Dettmer, Susan; Berberich, Anne; Keßler, Tobias; Karapanagiotou-Schenkel, Irini; Wick, Antje; Winkler, Frank; Pfaff, Elke; Brors, Benedikt; Debus, Jürgen; Unterberg, Andreas; Bendszus, Martin; et al. (Neuro-Oncology, 2019)
AbstractBackground. Patients with glioblastoma without O6-methylguanine-DNA methyltransferase (MGMT) promoter hypermethylation are unlikely to benefit from alk
Published: 01 October 2018
Im Titel ist die Ziffer 2 hochgestellt
Gesehen am 26.06.2019